The Ways for Prevention and Solving Problem of the Teacher’s Sexual Harassment to Student - Lanlod, Yanyong (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The purposes of this article were 1. to study the results of the teacher’s sexual harassment to the students 2. to study the causes and ways for prevention and solving problem of the teacher’s sexual harassment to student. It is found that sexual harassment with learners has failed by nature to the principle of teaching professional convention as well as morality and teacher’s discipline. The offender will receive disciplinary punishment ranging from level of the lightest to the strongest severity: the criminal penalty sine fine money imprisonment until execution. The Ministry of Education has announced for punishment sexual culprit teachers to students many cases. The causes of the teacher’s sexual harassment to the students are as follows; 1. teachers have power over their students; 2. teachers have relations with some influencer in the local; 3. parents of the students are unlikely to defend the cases; 4. the cronyism in the school; 5. teachers’ lack of consciousness to own roles and duties; 6. teachers’ sexual obsession; 7. desires caused by physical appearance 8. teachers’ mental problems and 9. lack of supervisors’ disciplinary and consciousness enforcement. The overall ways for prevention and solving the problems are as follows; 1. modification teacher’s behavior and mindset; 2. modification of the effective structure to sexual misconduct of teachers; 3. teaching students about sexual safety and rights; 4. implementing Buddhism’s principle and 5. education administrator in all levels should be strict and implant moral and conscience to teachers.